PHILOSOPHY ANALYSIS OF THE ROLE OF PASTORS AND PARENTS IN EDUCATING CHILDREN AND YOUTH AGGARES ON EDUCATIONALLEVEL IN CHURCH BASED ON 22: 6 IN GMAHK-7 JEMAAT PADASUKA CIMAHI, BANDUNG - Josua Siahaan; Stimson B. Hutagalung (Jurnal Koinonia, 2019)
The author examines "The role of pastors and parents in educating children and adolescents in improving education in the church" in the Padasuka congregation, Cimahi, Bandung, and the application of this verse context in the church itself.This research was specifically addressed to the Padasuka congregation, Cimahi. Bandung. The research has 4 indicators, namely: (1) "The role of the pastor in educating children and adolescents in the church", (2) "Actions taken by parents in educating children and adolescents in the church", (3) "The concept of educating children and Youth in the Bible ", and (4)" Getting education that is in the Church".The researcher has a basis with four indicators to be discussed, namely: The role of the pastor in educating children and adolescents in the church. The second indicator is about actions taken by parents in educating children and adolescents in the church. The third indicator concerning the concept of educating children and adolescents in the Bible, and the fourth indicator is about obtaining education in the ChurchThis research is divided into two parts, namely theoretical research and field research. The results of theoretical research are the role of pastors in educating children and adolescents in the church. Actions taken by parents in educating children and adolescents in the church. The concept of educating Children and Youth in the Bible. Get education in theChurch.The results of field research conducted through questionnaires were distributed to 35 members of the Padasuka Seventh-day Adventist Church, Cimahi, Bandung, where the questionnaire contained 45 questions, resulting in a data that could be concluded that the respondents had very good views on the one to four.The method that I use to complete this scientific work is by the method of collecting data through: the Bible, books, magazines, dictates, reflections, interviews, the internet, and other articles relating to the writing of this scientific paper.